South Bedroom, Gothic Suite (1926)
Interior view of the South Gothic bedroom in Casa Grande (Main House). Bedroom features a 14th century Spanish Gothic ceiling from Teruel, Spain. This became W.R. Hearst's bedroom in 1927, when he and Marion Davies moved into the Gothic Suite from Casa del Mar (House A).